2021
DOI: 10.1111/medu.14666
|View full text |Cite
|
Sign up to set email alerts
|

Student ethnicity predicts social learning experiences, self‐regulatory focus and grades

Abstract: Context: Ethnic minority students find that their ethnicity negatively affects the evaluation of their capacities and their feelings in medical school. This study tests whether ethnic minority and majority students differ in their 'self-regulatory focus' in clinical training, that is, their ways to approach goals, due to differences in social learning experiences. Self-regulatory focus consists of a promotion and prevention focus. People who are prone to stereotypes and unfair treatments are more likely to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Indeed, research has indicated that ethnic minority students have more perceptions of unfair treatment when they are in medical school. 27,28 An alternative reason for the finding that applicants with minority backgrounds did not have more negative perceptions towards certain selection methods is that previous studies mainly included eligible pre-university students who have not yet applied and could have based their perceptions on inaccurate or incomplete information. 3,11 Note: B refers to the unstandardised regression coefficient together with the standard error and the 95% confidence interval (95% CI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, research has indicated that ethnic minority students have more perceptions of unfair treatment when they are in medical school. 27,28 An alternative reason for the finding that applicants with minority backgrounds did not have more negative perceptions towards certain selection methods is that previous studies mainly included eligible pre-university students who have not yet applied and could have based their perceptions on inaccurate or incomplete information. 3,11 Note: B refers to the unstandardised regression coefficient together with the standard error and the 95% confidence interval (95% CI).…”
Section: Discussionmentioning
confidence: 99%
“…selection methods) similar regardless of their background, while applicants with sociodemographic minority backgrounds may have more negative perceptions regarding other components of procedural justice, such as interpersonal treatment. Indeed, research has indicated that ethnic minority students have more perceptions of unfair treatment when they are in medical school 27,28 . An alternative reason for the finding that applicants with minority backgrounds did not have more negative perceptions towards certain selection methods is that previous studies mainly included eligible pre‐university students who have not yet applied and could have based their perceptions on inaccurate or incomplete information 3,11 .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Comparisons between high and low-performing students on how they learn would help differentiate the effective and ineffective measures for learning. 20,21,22 Most of articles published in last five years focus on exploring the self-regulated learning of medical students during the clinical years, showing a growing interest in the area.…”
Section: Discussionmentioning
confidence: 99%